2002
DOI: 10.3928/0191-3913-20020701-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functions of the Parvocellular and Magnocellular Pathways in Strabismic Amblyopia

Abstract: Purpose: To evaluate the functions of the magnocellular and parvocellular pathways in strabismic amblyopia. Methods: Visual evoked potentials produced by achromatic and chromatic stimuli in 14 children with strabismic amblyopia were compared with those in 14 age-matched control subjects. The achromatic sine-wave grating with low spatial frequency was used to stimulate the magnocellular pathway, whereas the parvocellular pathway was stimulated by the chromatic sine-wave grating (isoluminant red-green)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Evaluation of the parvocellular and magnocellular pathways in strabismic or anisometropic amblyopia by visually evoked potentials has shown that the function of the parvocellular pathway in the amblyopic eye is selectively impaired [9,25]. Our results confirm these findings and further demonstrate that the impairment is selectively greater for the contra-lateral projections.…”
Section: Parvocellular and Magnocellular Pathwayssupporting
confidence: 84%
“…Evaluation of the parvocellular and magnocellular pathways in strabismic or anisometropic amblyopia by visually evoked potentials has shown that the function of the parvocellular pathway in the amblyopic eye is selectively impaired [9,25]. Our results confirm these findings and further demonstrate that the impairment is selectively greater for the contra-lateral projections.…”
Section: Parvocellular and Magnocellular Pathwayssupporting
confidence: 84%
“…In humans, the bulk of the data reports greater deficits in aspects of vision thought to be mediated by the P pathway (deficits for high spatial frequency stimuli: Bradley & Freeman, 1981; Hess & Howell, 1977; Levi & Harwerth, 1977, deficits for red/green chromatic stimuli: Davis, Sloper, Neveu, Hogg, Morgan, & Holder, 2006; Demirci, Gezer, Sezen, Ovali, Demiralp, & Isoglu-Alkoc, 2002; but see Zele, Pokorny, Lee, & Ireland, 2007). Corroborating the human results, studies of visually deprived animals have reported that morphological changes are greater within the P layers, compared to the M layers, of the LGN (Hendrickson et al, 1987; LeVay, Wiesel, & Hubel, 1980 and see von Noorden, Crawford, & Levacy, 1983 for greater P disruption in the LGN of a single human).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the notion that P pathway development relies more on visual experience than the M pathway come from studies investigating amblyopic adults who had abnormal visual experience during development. The bulk of those studies report greater deficits in aspects of vision thought to be mediated by the P pathway (Davis, Sloper, Neveu, Hogg, Morgan & Holder, 2006; Demirci, Gezer, Sezen, Ovali, Demiralp & Isoglu-Alkoc, 2002; but see Zele, Pokorny, Lee & Ireland, 2007). …”
Section: Introductionmentioning
confidence: 99%